Sociodemographic factors, mental health and social media: a comparative study on suicidal behavior - García-Martínez, Claudia; Ene-Gimeno, Séfora; Sáez-Martínez, Samara (Acciones e Investigaciones Sociales, 2023)
Introduction: Suicide is a growing public health problem. The aim of this study is to analyze suicidal ideation, planning and/or behavior in relation to sociodemographic factors, mental health status and use of social media, comparing a group of people with suicidal behavior and those without suicidal behavior, matched by sex and age. Methodology: A comparative longitudinal descriptive study was carried out. The outcome variable was suicidal behavior. Sociodemographic, mental health and social network use variables were also collected. Chi-square and Student’s T statistics were used and multivariate logistic regression was performed. Results: 102 subjects participated, 51 of them with suicidal ideation or attempt, and 51 of them without suicidal ideation. Significant differences were found between these groups in terms of sociodemographic variables and history of psychiatric diagnoses. According to the multivariate analysis, the factors associated with self-injurious behavior are not being working (studying, unemployed, retired, or with temporary or permanent disability) (B: 1.193, Odds ratio: 3.298), having a depressive episode in the previous year (B: -2.350, Odds ratio: 0.095), and an anxiety disorder (B: -1.659, Odds ratio: 0.190). The model has a Cox and Snell R-squared of 0.418. Conclusions: These results confirm the existence of a profile of people who may exhibit suicidal behavior. The different pattern of use of social media can be useful for instantaneous ecological risk assessment.